HỘI NHẬP VÀ HỢP TÁC TÀI CHÍNH Ở CHÂU Á ? CON ĐƯỜNG DẪN ĐẾN ĐỒNG TIỀN CHUNG CHÂU Á (ASIA CURRENCY UNIT) - Nhựt, Quan Minh (Tạp chí Khoa học Đại học Cần Thơ, 2005)
abstract In 1997 Asian crisis, there has been a surge of proposals for financial integration of Asian countries. An Asian Monetary Fund (AMF) was suggested by Japan in 1997 and the Chiang Mai Initiative (CMI) was agreed by the finance ministers of ASEAN+3 countries in May 2000. In addition, a major change has taken place in Asian countries due to traditional reliance on overseas borrowings and bank-intermediated financing. An increasing trend to view the direct issuance of securities, particularly bond issues by the government and the private sector, as a viable way of financing their projects, and of harnessing the budget deficit as an important and viable means of bringing about the emergence of a local debt market. The fact points out the relationship between the Asian countries has developed significantly, especially in regional integration of monetary and finance although there have been some obstacles on the way of cooperation. Keywords: Asian financial crisis, financial integration, financial cooperation, bond Title: Financial cooperation and integration in Asia ? The road to establishing Asia Currency Unit